Numerical Study of Flow Characteristics Inside Serrated Dodger Channels Using the Openfoam Program - Hafidh Farisi; Umboro Lasminto; Satria Damar Negara (Journal of Social Research, 2023)
The dodger building is one part of the dam component that serves to divert the flow of the river during construction work. One of the requirements for evasive buildings is to be able to drain river water well, so that the characteristics of the flow in the dodger channel need to be known to see how the flow conditions that occur in the dodge channel. This study aims to examine the flow characteristics of the Tapin Dam circumvention channel due to the design of the channel tunnel using a tooth shape, by modeling the relationship between the flow characteristics (velocity profile, pressure drop profile, and turbulent kinetic energy profile) of the jagged channel dimension shape using numerical computational analysis with the help of CFD (Computational Fluid Dynamics) software. From the modeling results, it will be known the influence of channel dimensions on flow characteristics in the dodger channel.